1996
DOI: 10.1177/106342669600400106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Instruction, Cooperative Learning, and Independent Learning Practices on the Classroom Behavior of Students with Behavioral Disorders

Abstract: The purpose of this study was to conduct a comparative analysis of the effects of direct instruction, cooperative learning, and independent learning instructional practices on the classroom behavior of students with behavior disorders. Results indicated that there were distinct differences in the classroom behavior of the students during the direct instruction condition. In this condition, they displayed higher rates of on-task behavior and lower rates of disruptive behavior relative to the cooperative learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 16 publications
2
26
0
1
Order By: Relevance
“…Research suggests that a systematic response to low levels of misbehavior can effectively reduce coercive interactions and maintain appropriate behavior by intervening early in the chain of events (see Cypress Group, 1996;Kauffman, 1999b;Nelson, 1996). The teachers' three-tiered cooldown system (see Table 2) was consistent with this model.…”
Section: Description Of the Programsupporting
confidence: 60%
See 1 more Smart Citation
“…Research suggests that a systematic response to low levels of misbehavior can effectively reduce coercive interactions and maintain appropriate behavior by intervening early in the chain of events (see Cypress Group, 1996;Kauffman, 1999b;Nelson, 1996). The teachers' three-tiered cooldown system (see Table 2) was consistent with this model.…”
Section: Description Of the Programsupporting
confidence: 60%
“…(p. 5). Well aware of the importance of using empirically based methods like teacher-directed instruction (Engelmann & Carnine, 1991;Nelson, Johnson, & Marchand-Martella, 1996;Porter & Brophy, 1988;Wehby, Symons, Canale, & Go, 1998;White, 1988) and cognitive strategy instruction (Deshler, Ellis, & Lenz, 1996;Wood, Woloshyn, & Willoughby, 1995), the teachers employed these methods consistently in all subject areas. The team-teaching arrangement allowed as many as four instructional groups to be operating simultaneously under the direction of one of the adults.…”
Section: Description Of the Programmentioning
confidence: 99%
“…In total, 17 studies were found for this review which highlight what researchers have found in this area. Five of these studies (Behets, 1997;Goolsby, 1996;Nelson, Johnson, & Marchand-Martella, 1996;Stright & Supplee, 2002;Vasquez-Levy, 1993) concern whole-class instruction, whereas four others (Christenson & Serrao, 1997;Hannifin & Clark, 1989(as cited in Webb, Baxter, & Thompson, 1997Harwood, 1995;Hooper, Ward, Hannafin, & Clark, 1989) present cooperative learning strategies. Looking at these earlier studies provided a pathway to substantiate the importance of the present study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers investigated the treatment effects of three types of behaviour management evaluation methods – teacher evaluation, self‐evaluation, and group evaluation – on both the academic and the behaviour performance of three students with EBD. In another study, Nelson and Johnson (1996) conducted a comparative analysis of the effects of direct instruction, co‐operative learning and independent learning practices on the classroom behaviour of students with behavioural disorders. In both studies researchers were interested in examining the impact of more than one independent variable on the dependent variables.…”
Section: Single Subject Research: Questions Mattermentioning
confidence: 99%